2015
DOI: 10.5430/wje.v5n1p102
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Training Programmes of Polytechnics in Ghana: The Pertinent Issues

Abstract: In today's world of stiff competition in the labour market, coupled with advanced technology, industries require of students to have job experience before employing them. The challenge here is that the experience being required is not taught in the lecture rooms. The reality is that, it is only gained though hands on the job, thus real world confrontation popularly called industrial attachment a platform for students arm themselves with all the skill, knowledge and demanded experience. This article examines th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(40 citation statements)
references
References 10 publications
10
29
1
Order By: Relevance
“…To empower industrial training programs, vocational institutions need some ideas for continuous quality improvement, such as providing appropriate training content (Jalani et al, 2016). According to (Nduro et al, 2015), to improve the quality of industrial training programs, a stakeholder's meeting could be organized rapidly to know what industries expect from interns.…”
Section: Improvement Of Collaborationmentioning
confidence: 99%
“…To empower industrial training programs, vocational institutions need some ideas for continuous quality improvement, such as providing appropriate training content (Jalani et al, 2016). According to (Nduro et al, 2015), to improve the quality of industrial training programs, a stakeholder's meeting could be organized rapidly to know what industries expect from interns.…”
Section: Improvement Of Collaborationmentioning
confidence: 99%
“…This is in line with Kokt and Strydom (2014), who agree that industry practitioners expect hospitality graduates to be qualified and be able to cope with challenges that they encounter. Nduro et al (2015) also divulged that a more significant part of the skill set required for the hospitality industry could be gained through hands-on training. Hence, it is fundamental for hospitality education to create more opportunities to allow students pursuing programs in hospitality management to undertake regular industrial attachments to equip them with competencies expected by the industry.…”
Section: Discussionmentioning
confidence: 99%
“…However, with an increase in students' enrolment, Industrial Attachment became a big problem (Imoro & Acortsu 2015). Before the year 2006, the Institution engaged students in industrial tours and students were asked to write reports which were marked (Nduro, 2015;Imoro & Acortsu 2015;Tamale Technical University, 2018;Adjei et al, 2014). Imoro & Acortsu (2015) indicated that on the 30th November 2004, there was a meeting for all Liaison Officers at the Civil Servants Association auditorium in Accra.…”
Section: Historical Precedencementioning
confidence: 99%
“…We were informed that, the National Board for Professional and Technical Examination (NABPTEX) had taken an oversight responsibility of Industrial Attachment (Imoro & Acortsu, 2015;Adjei et al, 2014). The then Executive Secretary, promised to organize a special training programme for all Liaison Officers but that promise never materialized (Imoro & Acortsu, 2015;Nduro, 2015;Tamale Technical University, 2018).…”
Section: Historical Precedencementioning
confidence: 99%
See 1 more Smart Citation